The Evaluation of a Method for Adenosine Diphosphate Induced Platelet Aggregation in the Guinea Pig - Mackenzie, R. D; Henderson, J. G; Steinbach, J. M (Thrombosis and Haemostasis, 1971)
A method is described for the in vivo measurement of ADP-induced platelet aggregation in the guinea pig. This method uses the property of the lungs to remove platelet aggregates from the circulation. ADP is infused into the jugular vein and blood samples are removed from the carotid artery for determination of platelet concentration.In order to find a practical concentration of ADP and infusion time, the effects of several concentrations and infusion time on platelet count versus time were determined. A dose of 0.2 mg/kg ADP infused over 1 min was found to produce an approximately 50% drop in platelet count with a return to the original level at about 30 min. The analysis of the platelet response to ADP can be made quantitative by measurement of the total response, that is, the total decrease of platelet count from start of infusion to the return to preinfusion values.Prostaglandin E1 was tested and found to inhibit the total aggregation response with this method.